A Randomized, Sham-Controlled Trial on the Efficacy and Safety of Electroacupuncture for Lumbar Disc Herniation with Radiculopathy: Rationale and Study Protocol - Yang Y; Liu L; Yuan L; Liu X; Ding H; Zhou X; Cao Q (Journal of Pain Research)
Yuwei Yang,1,* Liting Liu,1,* Lixia Yuan,1 Xiaoya Liu,1 Haoying Ding,2 Xu Zhou,3 Qianan Cao4 1Graduate School, Jiangxi University of Chinese Medicine, Nanchang, Jiangxi, 330004, People’s Republic of China; 2The First Department of Acupuncture and Moxibustion, The Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, Jiangxi, 330004, People’s Republic of China; 3Evidence-Based Medicine Research Center, Jiangxi University of Chinese Medicine, Nanchang, Jiangxi, 330004, People’s Republic of China; 4Acupuncture and Moxibustion Rehabilitation Center, The Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, Jiangxi, 330004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qianan Cao, Acupuncture and Moxibustion Rehabilitation Center, The Affiliated Hospital of Jiangxi University of Chinese Medicine, ba Yi Avenue No. 445, Nanchang, Jiangxi, 330004, People’s Republic of China, Tel +8618720928675, Fax +86079186210551, Email 18720928675@163.com Xu Zhou, Evidence-based Medicine Research Center, Jiangxi University of Chinese Medicine, Mei Ling Avenue No. 1688, Nanchang, Jiangxi, 330004, People’s Republic of China, Tel +8618870050733, Fax +86079187118012, Email zhouxu_ebm@hotmail.comIntroduction: Electroacupuncture, validated in preclinical studies, is a promising alternative approach for lumbar disc herniation with radiculopathy (LDHR). This trial aims to evaluate the efficacy and safety of electroacupuncture in patients with LDHR.Methods: This randomized, single-blind, sham-controlled trial will enroll 170 participants diagnosed with LDHR and who present Numerical Rating Scale (NRS) scores ≥ 4 for both lower back and leg pain. Participants will be allocated at a 1:1 ratio to receive either electroacupuncture or sham electroacupuncture (superficial needling at nonacupoint sites). The sample size was determined based on pilot study data and power calculations. Treatments will be administered three times weekly over 8 weeks (24 sessions total), with blinding maintained throughout. An 18-week noninterventional follow-up will be extended to address the knowledge gap regarding the durability of neuromodulatory effects of electroacupuncture. The following outcomes will be evaluated: 1) primary outcome: the proportion of responders achieving ≥ a 2-point NRS reduction in both lower back and leg pain from baseline at weeks 8 and 24; 2) secondary outcomes: changes from baseline at weeks 4, 8, 16, and 24 in the intensity of low back pain and leg pain, level of disability, severity of depression and anxiety, sleep quality, as well as the incidence of lumbar spine surgery and the proportion of use of analgesics at weeks 8 and 24; and 3) safety outcome: the incidence of adverse events. The efficacy outcomes will be analyzed based on the full analysis set with the modified intention-to-treat principle. Treatment effects will be estimated using a generalized linear mixed-effects model for repeated measures. Blinding validity will be assessed via James’s and Bang’s indices.Conclusion: This rigorously designed randomized controlled trial will generate confirmatory evidence to support the efficacy and safety of electroacupuncture in the treatment of LDHR.Trial Registration No.: NCT06611332 (https://clinicaltrials.gov/study/NCT06611332).Keywords: electroacupuncture, lumbar disc herniation, radiculopathy, sham control, randomized controlled trial